Family member eating assistance and food intake in long‐term care: A secondary data analysis of the M3 Study. (4th September 2020) - Wu, Sarah A.; Morrison‐Koechl, Jill; Slaughter, Susan E.; Middleton, Laura E.; Carrier, Natalie; McAiney, Carrie; Lengyel, Christina; Keller, Heather
Abstract: Aim: To determine if protein and energy intake is significantly associated with a family member providing eating assistance to residents in long‐term care homes as compared with staff providing this assistance, when adjusting for other covariates. Background: Who provides eating support has the potential to improve resident food intake. Little is known about family eating assistance and if this is associated with resident food intake in long‐term care. Design: Cross‐sectional, secondary data analysis. Methods: Between October and January 2016, multilevel data were collected from 32 long‐term care homes across four Canadian provinces. Data included 3‐day weighed/observed food intake, mealtime observations, physical dining room assessments, health record review, and staff report of care needs. Residents where family provided eating assistance were compared with residents who received staff‐only assistance. Regression analysis determined the association of energy and protein intake with family eating assistance versus staff assistance while adjusting for covariates. Results: Of those residents who required any physical eating assistance ( N  = 147), 38% ( N  = 56) had family assistance during at least one of nine meals observed. Residents who received family assistance ( N  = 56) and those who did not ( N  = 91) were statistically different in several of their physiological eating abilities. When adjusting for covariates, family assistance was associated with significantly higher consumption of protein and energy intake. Conclusion: Energy and protein intake is significantly higher when family provides eating assistance. Family are encouraged to provide this direct care if it is required. Impact: Residents who struggle with independent eating can benefit from dedicated support during mealtimes. Findings from this study provide empirical evidence that family eating assistance is associated with improved resident food intake and provides strong justification to encourage families to be active partners in the care and well‐being of their relatives. Home administrators and nursing staff should support the specialized care that families can provide at mealtimes. 摘要: 目标: 确定在调整其他协变量时, 蛋白质和能量的摄入是否与向长期待在护理院的人员提供进食帮助的家庭成员与提供这种帮助的工作人员相比是否存在显著相关性。 背景资料: 提供进食帮助的人员能大幅提高护理院人员的进食量。我们对于家庭进食帮助及其与待在长期护理院内人员的进食帮助有无关联的知识知之甚少。 设计: 横断面分析, 二次数据分析。 方法: 2015年10月至2016年1月间, 从加拿大四个省的32家长期护理院收集了多层次数据。数据包括3天称重/观察的进食量、进餐时间观察、实际餐厅评估、健康记录审查和员工护理需求报告。将由家庭成员提供进食帮助的护理院人员与只接受护理院工作人员进食帮助的护理院人员进行比较。在调节协变量时, 回归分析确定了能量和蛋白质摄入量与家庭成员提供进食帮助和工作人员提供进食帮助的关系。 结果: 在那些需要任何实际进食帮助的护理院人员中(N=147人), 38%(N=56人)在观察的九顿饭中至少有一顿由家庭成员提供进食帮助。接受家庭成员进食帮助的护理院人员(N=56人)和没有接受家庭成员进食帮助的护理院人员(N=91人)在一些生理进食能力上存在统计学上的差异。当调节协变量时, 家庭成员提供进食帮助与蛋白质和能量摄入的显著增加有关。 结论: 当家庭成员提供进食帮助时, 能量和蛋白质的摄入量会显著增加。鼓励家庭成员在需要时提供这种直接的护理。 影响: 难以独立进食的疗养院人员可以在进餐时得到专门的支持。这项研究的发现提供了实验性证据, 表明家庭成员提供进食帮助与疗养院人员食物摄入的改善有关, 并为鼓励家庭成员积极参与亲属的照料和福祉提供有力的理由。疗养院管理人员和护理人员应支持家庭成员在用餐时提供的专业护理。